Analysis of Case 1 of the 5th High Lift Prediction Workshop with Ansys Fluent (2024)
The study for the airflow surrounding aircrafts has been for decades a vital component for businesses and organizations, however, most studies on airflow have been done experimentally in a wind tunnel and calculated without the assistance of technology. Now a days this has changed, and computational fluid dynamics (CFD) has become as important as experimental studies. Taking this into account, the American Institute of Aeronautics and Astronautics (AIAA) has developed over the last years a series of workshops with the purpose of creating better and more accurate simulations to predict the aerodynamic characteristics of the aircrafts’ wings. The present project shows and discusses the simulations required for the test case 1 of the 5th High Lift Prediction Workshop (HLPW), where experimental data obtained from the wind tunnel was compared with the results of these CFD simulations at “free air” condition. The geometry worked was the CRM-HL Wing Body (CRM-HL-WB) configuration and was provided by the workshop. This model does not have empennage or flap fairings, and the mesh used for the project was provided by the workshop for direct use in ANSYS FLUENT 2023 R1. The simulations used the turbulence model Spalart Allmaras (SA), for the 11° Angle of Attack (AoA) as requested by the workshop, but also other simulations were done for angles of attack from 6° to 20°. The results obtained from the CFD simulations showed great accuracy according to the experimental data; this result was the convergence of the aerodynamic forces of the model. Additionally, post-processing results of other physical variables were done, the results shown are pressure coefficient contour, skin friction coefficient contour, and velocity streamlines.